Well-to-wheel analysis of energy consumption, greenhouse gas and air pollutants emissions of hydrogen fuel cell vehicle in China - Wang, Qun; Xue, Mianqiang; Lin, Bin-Le; Lei, Zhongfang; Zhang, Zhenya (Journal of Cleaner Production, 2020)
Hydrogen fuel cell vehicle (HFCV) is considered as a promising solution for reducing greenhouse gas (GHG) and air pollutants emissions and improving energy security in the transportation sector. This study presents a well-to-wheel (WTW) analysis to estimate the WTW fossil fuel consumption, GHG emission and air pollutants emissions of VOCs, CO, NOx, SOx, PM2.5 and PM10 for HFCV under 12 hydrogen pathways in China for the current (2017) and near future (2030). The results were compared with the gasoline-fueled internal combustion engine vehicle (gasoline-ICEV) and battery electric vehicle (BEV) counterparts. The results show that HFCV can reduce 11–92% fossil fuel consumption compared with gasoline-ICEV in 2017, with one exception that HFCV based on on-site water electrolysis by grid electricity in which fossil fuel consumption increased by 10% instead. Compared with BEV, HFCV based on by-product hydrogen from chlor-alkali process and renewable water electrolysis have the fossil fuel consumption reduction benefits. Regarding GHG emissions, HFCV based on water electrolysis using the renewable electricity performs the best with a value of 31 g CO2-eq/km while that based on on-site water electrolysis using grid electricity performs the worst with a value of 431 g CO2-eq/km in 2017. For air pollutants, HFCV based on all hydrogen pathways can achieve a significant reduction of VOCs and CO emissions on a WTW basis, in comparison with gasoline-ICEV in 2017. In terms of NOx, SOx, PM2.5 and PM10, HFCV based on on-site water electrolysis by grid electricity electrolysis has the highest emissions due to high emission factors of the electricity generation process. Moreover, due to increased share of renewable electricity and improvement in the fuel economy, reductions in WTW fossil fuel consumption and pollutants emissions are excepted by 2030. This study indicates the importance of hydrogen production when considering the energy and environment performance of HFCV to ensure a life cycle low carbon and air pollutants emissions. •Well-to-wheel analysis of hydrogen fuel cell vehicle under various H2 pathways in China.•Fossil fuel consumption, GHG and criteria air pollutants emission are examined.•Hydrogen pathways are critical for emission reduction.•Air pollutants mitigation characteristics are identified.•Highlight the importance of incorporating well-to-tank stage into the comparison.